Estimation of carbon stocks under different soil uses in the central highlands of Mexico (2017)
The loss of organic carbon stocks from the soil and their expulsion into the atmosphere due to the effect of anthropogenic activities must be understood as a problem that goes beyond the environmental to the social and economic context, with the soil degradation being just one of its many impacts. While the accumulation of carbon in the soil depends naturally on the interaction among a series of biotic and abiotic factors, management practices often cause the deterioration of its physical, chemical and biological properties, and, thus, increase the levels of mineralization and a reduction in carbon stocks. This research was undertaken in the municipality of San José del Rincón, State of Mexico, in volcanic soils under different conditions of soil use and disturbation time periods. Samples were obtained at 11 plots, on which physical and chemical analyses were undertaken, obtaining soil organic carbon stocks at 20 cm top soil. The results indicated that, for the soils used for agriculture and induced pasture, there were significant increases in the bulk density, greater acidity and a decrease in carbon concentration compared to forest soils. The organic carbon stocks taken from soils used in forestry, agriculture and induced pasture at a depth of 20 cm were 131, 53 and 63 Mg C ha-1 respectively, results which suggest the timing and intensity of management are determinants in the loss of soil organic carbon stocks from the soil, as well as the alteration of some of their physical and chemical properties.